Pengaruh Penggunaan Gadget Terhadap Interaksi Sosial Anak Usia 5-6 Tahun - Dinda Berliana; Laily Rosidah; Tri Sayekti (Institut Agama Islam Negeri Madura, 2022)
This study aims to determine the influence of using gadget on the social interaction of children 5-6 years at TKIT Al-Muhajirin Cilegon-Banten. This study uses quantitative research with ex-post facto methods. Data collection techniques using questionnaires and documentation. The population in this study were 60 parents who had children aged 5-6 years at TKIT Al-Muhajirin and the sampling technique used a total sampling where the number of samples taken was the same as the total population is 60 people. The data analysis technique used correlation coefficient test, determination coefficient test, simple linear regression, and t-test. The results of this study indicate that using gadgets has a significant effect on children’s social interactions. This can be seen from the results of the hyphotesis testing obtained a significance value is 0.001 < 0.05 and the t value is -3.422, tcount value is 3.422 > t table 2.001 so it can be concluded that H0 is rejected and H1 is accepted which means that there is an influence of using gadgets on social interaction of children aged 5-6 years at TKIT Al-Muhajirin Cilegon-Banten.